(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
The increasing abuses and human rights’ restrictions whose Afghan women are victims arise the question as to what remedies are provided by international law in order to address this dramatic situation. To answer this question the paper focuses first on the role played by the United Nations, that in 2002 established the United Nations Assistance Mission in Afghanistan (UNAMA), which was entrusted to implement and to monitor the application of human rights in the State. Secondly, it seeks to frame the legal obligations that international law place upon States, and upon Afghanistan in particular, as regards the protection of women’s rights, in order to finally question, both in a de iure condito and in a de iure condendo perspective, the effectiveness of the remedies provided by international law in addressing the continuous and systematic violations of international human rights perpetrated against Afghan women